Minutes of 16th technical and progress monitoring (TPM) meeting of BRACU new campus (session II) - Brac University (Brac University, 2023)
Minutes of the 16th Technical and Progress Monitoring (TPM) meeting (session Il) of BRACU new campus, held on 26th May, 2019.